2019
DOI: 10.3847/1538-4357/aaeffb
|View full text |Cite
|
Sign up to set email alerts
|

First Resolution of Microlensed Images*

Abstract: We employ VLTI GRAVITY to resolve, for the first time, the two images generated by a gravitational microlens. The measurements of the image separation ∆θ −,+ = 3.78 ± 0.05 mas, and hence the Einstein radius θ E = 1.87 ± 0.03 mas, are precise. This demonstrates the robustness of the method, provided that the source is bright enough for GRAVITY (K 10.5) and the image separation is of order or larger than the fringe spacing. When θ E is combined with a measurement of the "microlens parallax" π E , the two will to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 45 publications
2
82
0
Order By: Relevance
“…The combination of photometry and astrometry is powerful not only for BH lenses, but also for obtaining precise mass measurements of any type of lens, as was shown with the first astrometric microlensing signal detected outside our Solar System (Sahu et al 2017). Another method of breaking degeneracies is to have the ability to resolve the images themselves, which is possible for stellar-mass lenses using interferometric techniques (Dong et al 2019).…”
Section: Hunting For Bhsmentioning
confidence: 98%
See 1 more Smart Citation
“…The combination of photometry and astrometry is powerful not only for BH lenses, but also for obtaining precise mass measurements of any type of lens, as was shown with the first astrometric microlensing signal detected outside our Solar System (Sahu et al 2017). Another method of breaking degeneracies is to have the ability to resolve the images themselves, which is possible for stellar-mass lenses using interferometric techniques (Dong et al 2019).…”
Section: Hunting For Bhsmentioning
confidence: 98%
“…For context, the highest-resolution images from the largest ground-based or space-based telescopes (with a filled aperture) is 50 mas in the optical or infrared. However, in some cases Einstein radii of this scale are interferometrically resolvable (Dong et al 2019), moving from the regime of microlensing to strong lensing. The Einstein crossing time t E , the time it takes for the lens to traverse the Einstein radius, can be inferred from the photometric light curve.…”
Section: Candidate Selection Parametersmentioning
confidence: 99%
“…However, because of the degeneracy between the absolute mass and distance of the lens system, they estimated them using a stochastic technique based on a Galactic model such that the planetary mass is 9.2±6.6M ⊕ , the host star's mass is ∼0.25M e , and the distance to the system is ∼380pc. On the other hand, Dong et al (2019) measured the angular Einstein radius θ E of this event by observing the separation of the two microlensed source star images using the VLTI/GRAVITY instrument. They confirmed that the θ E value estimated by Nucita et al (2018) is largely consistent with the value measured by VLTI, although they did not attempt to improve the physical parameters of the lens system using the improved θ E .…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advent of long baseline optical interfereometers (Delplancke et al 2001), these scales have now become observable and just beginning to be within sensitivity limits for the world's most capable instruments. Indeed the potential for progress employing this approach was recently demonstrated by Dong et al (2019) who achieved single-epoch observation of a microlensing event using the Gravity beam combiner at the VLTI interferometer, proceeding to show that useful con-E-mail: geraint.lewis@sydney.edu.au straints on the physical parameters of the event could be obtained from the data.…”
Section: Introductionmentioning
confidence: 99%